Just dying: the futility of futility. - Savulescu, J (2013)
I argue that Brierley et al are wrong to claim that parents who request futile treatment are acting against the interests of their child. A better ethical ground for withholding or withdrawing life-prolonging treatment is not that it is in the interests of the patient to die, but rather on grounds of the limitation of resources and the requirements of distributive justice. Put simply, not all treatment that might be in a person's interests must ethically be provided.